History and Development of the Bugis Tribe in Karangantu Banten in 1984-2022 - Sunandar, Muhamad Nandang; Setiawan, Robi (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2024)
This study investigated one of Indonesia's ethnicities, namely the Bugis Tribe from Makassar, in Karangatu, Banten. This study aims to uncover the Bugis tribe's first arrival in Banten, its subsequent development, and its role in Karangatu, Banten. Methodologically, participant observation, historical analysis, and ethnographic research were used. To determine the origins and development of the Bugis Tribe in Karangatu, interviews were conducted with Bugis leaders, academics, and practitioners, along with archival research. The main findings of this study highlight how the Bugis tribe traveled to Karangatu, Banten, and built their villages there. This research also emphasizes how the Bugis tribe interacts with other tribes in Karangatu, Banten. The main conclusion of this study is that the Bugis tribe is known not only as a sailing tribe but also as one with a strong work ethic in the marine field (as fishermen) and as able to synergize with other tribes. It is a form of tolerance and cross-cultural contact. By providing insights into the blend of spirituality, culture, and religion in Indonesia, this study enriches the discipline. It provides a sophisticated interpretation of the importance of studying the Bugis Tribe's historical development in Karangatu, Banten, to better understand tolerance and cross-cultural communication.